If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4 + 2v = 4(v + -4) Reorder the terms: -4 + 2v = 4(-4 + v) -4 + 2v = (-4 * 4 + v * 4) -4 + 2v = (-16 + 4v) Solving -4 + 2v = -16 + 4v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-4v' to each side of the equation. -4 + 2v + -4v = -16 + 4v + -4v Combine like terms: 2v + -4v = -2v -4 + -2v = -16 + 4v + -4v Combine like terms: 4v + -4v = 0 -4 + -2v = -16 + 0 -4 + -2v = -16 Add '4' to each side of the equation. -4 + 4 + -2v = -16 + 4 Combine like terms: -4 + 4 = 0 0 + -2v = -16 + 4 -2v = -16 + 4 Combine like terms: -16 + 4 = -12 -2v = -12 Divide each side by '-2'. v = 6 Simplifying v = 6
| 2x+6+3x=7+2x+8 | | 5z+8z=Z-2-9z | | 10=5+v | | 8x+9=6x+32 | | -5/4x-2=-8 | | 2(6)+4y=24 | | y=1/2cos2x | | -20=1/3n-10 | | 212-3=53 | | 2(4)+4y=24 | | 3/50=x/5280 | | (1/65)=(1/x) | | 1+2r+8r=1+7r+8+4 | | y+26=-5 | | 5x+4x=40 | | 6b+10b-7= | | 10n-3=-2 | | 2(x+7)+x=6x+10 | | 72+x-x^2=0 | | 2(2)+4y=24 | | 6(3-4n)-3n=18 | | 24-6r=6[4-r] | | 25y+5x=30yx | | 14x+16=9x+14+52 | | 2(1)+4y=24 | | x^3-7x^2-8x=2 | | 20x=x^2+5 | | 2x(x+7)+x=6x+10 | | 7/5000=x/78000 | | x^3-7x^2-8x+2=0 | | 5[y-2]-2=2[y+1]-5 | | 8x+2=2x-7x |